Strategies and leadership values in Obama's apology discourse - Varma, Susanna Bithiah; Paramasivam, Shamala; Nimehchisalem, Vahid (Walter de Gruyter GmbH, 2020)
This study analyses leadership apologies to gain insights into effective leadership performance from the perspective of apologising. The study explores Obama’s leadership qualities that are projected through his apology discourse mainly the strategies used to construct his apologies and values that emerge from them. The study concluded that leadership should be versatile for a leader to be able to perform efficiently in crucial situations. It is important for a leader to have the ability to blend strategies to display good values to perform the speech act of apology well because in doing so, they will be able to bind themselves in good rapport with their followers which creates unity in the relationship. The significance of the study can be viewed in the potential to reframe apology as an empowering act that can positively impact leaders’ image rather than an act that is viewed as taboo or ineffective for leadership.